Hospital Performance and Operational Management: A Bibliometric Review of Key Factors Affecting Effectiveness - Alifah Wilanda; Rival Pahrijal; Ilham Akbar Bunyamin (Westscience Press, 2024)
This study employs bibliometric and co-authorship network analyses to investigate the landscape of research in hospital performance and operational management. Using VOSviewer, key themes were visualized to depict the concentration and evolution of research areas from technology integration to quality management within healthcare settings. The study identifies central researchers and maps collaborative networks, revealing both densely interconnected groups and isolated researchers. Practical implications are discussed for academic researchers, hospital administrators, and policymakers, highlighting areas for strategic development and potential collaboration. Limitations such as selection bias and the exclusion of qualitative impact underscore the need for cautious interpretation of the results. The study provides a foundational tool for stakeholders to understand the current research environment and to guide future healthcare management practices effectively.